How to be an ocean scientist in your own home - Simon, Seymour; Carter, David A. (New York : Lippincott, 1988)
A collection of experiments, using easily available relatively inexpensive materials, designed to reveal the various characteristics of the oceans and the plants and animals that live in them.
Includes index.
Bibliography: p. 128-129.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
5.9
Keywords: Oceanography -- Experiments -- Juvenile literature; Experiments; Oceanography -- Experiments; Oceanography -- Experiments